Totally absorbable pdo-p4hb binary composite gradient degradation hernia repair patch
Patent Information
- Application Number
- CN202610442534.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-03
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-04-03
AI Technical Summary
但这一设计同样存在多重技术缺陷:一是PP为不可吸收成分,长期留存体内会持续作为异物刺激周围组织,显著增加术后感染、血清肿、肠粘连等并发症发生率,尤其在感染性腹壁缺损场景下,异物残留会加剧炎症反应,导致修复失败;二是依赖可移除弹性金属元件或弹性环辅助实现术中展平与刚度需求,不仅增加手术操作步骤(如术后需二次取出元件),延长手术时间,还可能因金属元件与组织摩擦、压迫引发局部组织刺激,且金属与补片的连接部位易形成应力集中,从而增加补片边缘断裂、疝复发的风险
[0019]本发明的技术效果如下:本发明公开了一种全可吸收PDO-P4HB二元复合梯度降解疝修补补片,采用全可吸收且无免疫原性的PDO+P4HB合成材质复合,替代动物源材料与不可吸收材料,术后可通过水解、酶解完全降解为无毒产物排出体外,无任何异物留存,从根源上降低感染、粘连等并发症风险,可适配感染性腹壁缺损等复杂修复场景。依托两种材料本征力学性能的协同优势——PDO提供术中操作所需的短期高强度与刚度,P4HB保障术后长期柔韧性与抗撕裂性,无需额外金属或弹性辅助元件即可实现术中易展平、术后抗变形的性能需求,简化手术操作流程,同时避免应力集中导致的补片断裂、复发风险。通过特定的编织结构及参数设计,利用PDO更高的初始力学强度与刚度,显著提升补片术后短期支撑能力,可适配不同面积、不同受力强度的腹壁缺损场景。借助二者降解速率的固有差异(PDO降解速率略快于P4HB,PDO 3~4个月降解,P4HB 4~6个月降解),构建梯度降解结构,实现“前期高强度支撑(PDO主导)——中期柔韧性过渡(二者协同)——后期完全降解(P4HB收尾)”的动态适配过程,既满足术中操作对刚度的需求,又能匹配组织修复各阶段的力学与生物需求,兼顾支撑稳定性与组织长入效果。
Smart Images

Figure CN122351577B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical materials technology, specifically to a fully absorbable PDO-P4HB binary composite gradient degradation hernia repair patch. Background Technology
[0002] Hernia is a common disease in general surgery, requiring surgical repair of the damaged abdominal wall. Tension-free hernia repair has replaced traditional suturing due to its lower postoperative pain and recurrence rate. Hernia repair mesh is the core consumable material for this surgery. Mesh can be classified into non-absorbable mesh, absorbable mesh, and composite mesh according to its material. Among them, composite mesh, which combines multiple materials to balance mechanical support and biocompatibility, has become a hot topic in clinical research.
[0003] Currently, one approach to manufacturing composite patches involves combining natural biomaterials with biodegradable polymeric materials. For example, CN103877619B discloses a composite SIS tissue repair material. Through processes such as weaving and vacuum lamination, polydioxanone (PDO) is combined with porcine small intestinal submucosa (SIS) to prepare a hernia repair patch. The aim is to leverage the excellent tissue compatibility and anti-infective properties of SIS to create a microenvironment for cell adhesion and proliferation. Simultaneously, the biodegradable material PDO is synthesized to improve the tensile strength, flexural properties, and structural stability of the patch, addressing the insufficient mechanical properties of pure SIS patches. However, natural animal-derived biomaterials, represented by SIS, still have two major technological shortcomings: First, the source of raw materials is limited by animal donors, and the consistency of components and structures between different donors and processing batches is difficult to precisely control, leading to fluctuations in patch performance and affecting the stability of clinical repair effects. Second, even after decellularization, residual antigenic components cannot be completely eliminated, posing a potential immunogenic risk and potentially triggering mild local immune responses or inflammatory infiltration. Meanwhile, the degradation rate of such natural biomaterials is significantly affected by the microenvironment, such as pH and enzyme activity, and it is difficult to precisely match the degradation sequence with that of polymeric materials such as PDO. This can easily lead to two situations: either the biomaterial degrades too quickly, causing premature failure of the overall mechanical support of the patch, or the biomaterial remains for too long, causing a continuous tissue reaction. Either situation will affect the quality of the repair.
[0004] Another approach to manufacturing composite patches is to combine absorbable and non-absorbable materials. For example, CN102137634A discloses a transplant device that uses polymer polypropylene (PP) and absorbable polyglycolic acid (PGA) as the core materials. It is formed by weaving or knitting processes, and the edges are reinforced to improve tear resistance. At the same time, a removable elastic metal element or elastic ring is added to enhance the stiffness and flattening performance of the patch during implantation. After the PGA degrades, it forms a large-pore lightweight structure, thereby improving abdominal wall compliance. However, this design also has several technical drawbacks: First, PP is a non-absorbable component, and its long-term retention in the body will continuously irritate surrounding tissues as a foreign body, significantly increasing the incidence of postoperative complications such as infection, seroma, and intestinal adhesions. Especially in the case of infectious abdominal wall defects, foreign body residue will exacerbate the inflammatory response and lead to repair failure. Second, relying on removable elastic metal elements or elastic rings to assist in achieving the flattening and rigidity requirements during surgery not only increases the number of surgical steps (such as the need to remove the elements a second time after surgery) and prolongs the operation time, but may also cause local tissue irritation due to friction and pressure between the metal elements and tissues. In addition, stress concentration is easily formed at the connection between the metal and the patch, thereby increasing the risk of patch edge breakage and hernia recurrence.
[0005] Therefore, how to simultaneously improve the performance stability and biocompatibility of composite patches, while taking into account the ease of intraoperative operation and postoperative mechanical stability and tissue compatibility, has become a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention
[0006] To address the aforementioned technical problems, this invention provides a fully absorbable PDO-P4HB binary composite gradient degradation hernia repair patch.
[0007] This invention provides a fully absorbable PDO-P4HB binary composite gradient degradation hernia repair patch, comprising a patch body with a mesh structure, the patch body comprising the following parts: PDO support layer, wherein the PDO support layer is adhered to the abdominal wall surface layer; The P4HB toughness layer covers the PDO support layer on the side away from the abdominal wall and completely overlaps with the PDO support layer. Multiple composite connection nodes, wherein each composite connection node is connected at both ends to the PDO support layer and the P4HB toughness layer, respectively. An edge reinforcement ring surrounds the patch body and covers the edges of the PDO support layer and the P4HB toughness layer; Both the composite connection node and the edge reinforcing ring are made of PDO-P4HB blend material, and the mass ratio of PDO to P4HB in the edge reinforcing ring is 3:7 to 5:5, preferably 4:6.
[0008] Furthermore, the PDO support layer is woven from PDO monofilaments with a diameter of 0.15~0.2mm, preferably 0.18mm; the P4HB toughness layer is woven from P4HB monofilaments with a diameter of 0.2~0.25mm, preferably 0.22mm. And / or, the PDO support layer has hexagonal braided holes with a pore size of 0.8~1.2mm, preferably 1.0mm; the P4HB toughness layer has diamond braided holes with a pore size of 1.2~1.5mm.
[0009] Further, and / or, the length of the composite connection node is 0.35~0.45mm; And / or, the width of the edge reinforcing ring is 0.5~0.8mm.
[0010] Furthermore, the thickness of the patch body is 3.0~4.0mm, the thickness of the PDO support layer is 1.0~1.5mm, and the thickness of the P4HB toughness layer is 1.8~2.5mm.
[0011] Another aspect of the present invention provides a method for preparing the above-mentioned fully absorbable PDO-P4HB binary composite gradient degradation hernia repair patch, comprising the following steps: Layered molding: Specifically includes the following steps: (1) PDO support layer forming: PDO monofilaments with a diameter of 0.15~0.2mm are woven in a hexagonal weaving method. After weaving, they are heat-set to stabilize the pore size. Then they are cut to the required specifications to obtain the PDO support layer. (2) P4HB toughness layer forming: P4HB monofilament with a diameter of 0.2~0.25mm is woven in a weft knitting diamond mesh. After weaving, it is subjected to low temperature setting treatment and then cut to the same specifications as the PDO support layer to obtain the P4HB toughness layer. Composite connection: The PDO support layer and the P4HB toughening layer are aligned and stacked, and welded using a point-by-point hot pressing method to form multiple composite connection nodes made of PDO-P4HB blend material between the PDO support layer and the P4HB, so that the PDO support layer and the P4HB toughening layer form a composite double-layer mesh structure; wherein the hot pressing welding temperature is higher than the melting point of P4HB and within the lower limit range of the melting point of PDO; Edge reinforcement: An edge reinforcement ring made of PDO-P4HB blend material is formed at the edge of the double-layer mesh structure by injection molding. After cooling, the ring is polished and cleaned to obtain the patch body.
[0012] Furthermore, in the PDO support layer forming step, the temperature of the heat setting treatment is 90~95℃ and the time is 2min; And / or, in the P4HB toughness layer forming step, the low-temperature setting treatment is performed at a temperature of 40°C for 3 minutes.
[0013] Furthermore, in the composite joining step, the hot-press welding method is as follows: Under conditions of temperature 106~110℃ and pressure 0.2MPa, the material is pressed evenly at 5mm intervals, with each pressing and holding time being 2~3s; preferably, the temperature of the hot pressing welding is 108℃. Preferably, the composite joining step further includes the following steps: The double-layer mesh structure after hot-press welding was subjected to an interlayer peel test. Samples with a peel strength ≥5N / cm were selected for edge reinforcement, and the remaining samples were re-hot-press welded.
[0014] Furthermore, in the edge reinforcement step, the injection molding method is as follows: The double-layer mesh material is placed in an injection mold with a pre-reserved molding groove. Molten PDO-P4HB blend material is injected into the molding groove and injection molded at a temperature of 112~115℃ and a pressure of 5MPa. And / or, the cooling method is as follows: Place the injection-molded sample at 40~45℃ for 10 minutes; And / or, the polishing method is as follows: After cooling, remove any remaining flash from the mold using a medical-grade scalpel, and then lightly sand the edge reinforcement ring with sandpaper until the roughness is ≤0.8μm.
[0015] Furthermore, prior to the PDO support layer forming step, the following steps are also included: Material pretreatment: Medical-grade PDO particles and medical-grade P4HB particles are vacuum dried to a moisture content of ≤0.1%, and the dried PDO particles and P4HB particles are melt-spun to obtain PDO monofilaments and P4HB monofilaments, respectively. Preferably, the method for drying the medical-grade PDO particles is as follows: Dry at 80℃ and a vacuum of -0.09MPa for 4 hours; Preferably, the method for drying the medical-grade P4HB particles is as follows: Dry at 50℃ and -0.09MPa for 6 hours.
[0016] Preferably, the PDO monofilament is prepared as follows: dried PDO particles are melt-spun using a single-screw spinning machine at 120~130℃ to obtain PDO monofilaments with a diameter of 0.15~0.2mm; Preferably, the P4HB monofilament is prepared as follows: Dry P4HB particles were melt-spun at 80-90℃ using a single-screw spinning machine to obtain P4HB monofilaments with a diameter of 0.2-0.25mm.
[0017] Furthermore, following the edge enhancement step, the following steps are also included: Post-processing of finished product: The patch body is soaked in medical alcohol at room temperature for 30 minutes, rinsed with deionized water, and then freeze-dried under vacuum until the moisture content is ≤0.5% to obtain the patch.
[0018] Preferably, the freeze-drying method is as follows: Dry for 8 hours at a temperature of -40℃ and a vacuum of -0.09MPa.
[0019] The technical effects of this invention are as follows: This invention discloses a fully absorbable PDO-P4HB binary composite gradient degradable hernia repair patch. It uses a fully absorbable and non-immunogenic PDO+P4HB synthetic composite material to replace animal-derived materials and non-absorbable materials. Postoperatively, it can be completely degraded into non-toxic products through hydrolysis and enzymatic hydrolysis and excreted from the body without any foreign body residue, fundamentally reducing the risk of complications such as infection and adhesion. It is suitable for complex repair scenarios such as infected abdominal wall defects. Leveraging the synergistic advantages of the intrinsic mechanical properties of the two materials—PDO provides the short-term high strength and stiffness required during surgery, while P4HB ensures long-term flexibility and tear resistance after surgery—it achieves the performance requirements of easy flattening during surgery and resistance to deformation after surgery without the need for additional metal or elastic auxiliary components, simplifying the surgical procedure and avoiding the risk of patch breakage and recurrence caused by stress concentration. Through specific weaving structure and parameter design, utilizing the higher initial mechanical strength and stiffness of PDO, the short-term support capacity of the patch after surgery is significantly improved, making it suitable for abdominal wall defects of different areas and stress intensities. By leveraging the inherent difference in degradation rates between the two (PDO degrades slightly faster than P4HB, with PDO degrading in 3-4 months and P4HB in 4-6 months), a gradient degradation structure is constructed to achieve a dynamic adaptation process of "high-strength support in the early stage (PDO-dominated) - flexible transition in the middle stage (both synergistic) - complete degradation in the later stage (P4HB as the final step)". This not only meets the rigidity requirements of intraoperative procedures but also matches the mechanical and biological needs of each stage of tissue repair, taking into account both support stability and tissue ingrowth. Attached Figure Description
[0020] One or more embodiments are illustrated by way of example with reference to the accompanying drawings, and these illustrative examples are not intended to limit the embodiments. The term "illustrative" as used herein means "serving as an example, embodiment, or illustration." Any embodiment illustrated herein as "illustrative" is not necessarily to be construed as superior to or better than other embodiments.
[0021] Figure 1 This is a top view of the fully absorbable PDO-P4HB binary composite gradient degradation hernia repair patch prepared in Example 1.
[0022] Figure 2 This is a cross-sectional view of the fully absorbable PDO-P4HB binary composite gradient degradation hernia repair patch prepared in Example 1. Detailed Implementation
[0023] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Unless otherwise expressly stated, throughout the specification and claims, the term "comprising" or its variations such as "including" or "comprising of," etc., will be understood to include the stated elements or components, and does not exclude other elements or other components.
[0024] Furthermore, to better illustrate the present invention, numerous specific details are set forth in the following detailed embodiments. Those skilled in the art will understand that the present invention can still be practiced even without certain specific details. In some embodiments, materials, elements, methods, and means well known to those skilled in the art are not described in detail in order to highlight the spirit of the invention.
[0025] Unless otherwise specified, the raw materials and equipment used in the following examples can be purchased commercially.
[0026] Example 1 A fully absorbable PDO-P4HB binary composite gradient degradable hernia repair patch is prepared by the following method: S1: Material Pretreatment Medical-grade PDO particles (molecular weight 100~150kDa) were selected and dried at 80℃ and -0.09MPa vacuum for 4 hours. At the same time, medical-grade P4HB particles (molecular weight 100~120kDa) were selected and dried at 50℃ and -0.09MPa vacuum for 6 hours to ensure that the moisture content of both particles was ≤0.1%, thus avoiding the formation of bubbles, pinholes and hydrolytic degradation of materials due to the presence of moisture during processing. Dry PDO particles were melt-spun using a single-screw spinning machine at 120~130℃ to obtain PDO monofilaments with a diameter of approximately 0.18 mm. Dry P4HB particles were melt-spun at 80-90℃ using a single-screw spinning machine to obtain P4HB monofilaments with a diameter of approximately 0.22 mm.
[0027] S2: Layered molding (1) PDO support layer forming: PDO monofilament with a diameter of 0.18 mm is woven in a hexagonal weave with a weave density of 30 threads / inch in the warp and 28 threads / inch in the weft. After weaving, it is heat-set (temperature 90~95℃, time 2min) to ensure that the aperture is stable at 1.0 mm. Then it is cut to the required specifications to obtain the PDO support layer. (2) P4HB toughness layer forming: P4HB monofilament with a diameter of 0.2~0.25mm is used to weave in a weft knitting diamond mesh manner with a knitting density of 25 threads / inch in the warp and 23 threads / inch in the weft. After weaving, it is subjected to low temperature setting treatment (temperature 40℃, time 3min) to avoid damage to the toughness of P4HB. Then it is cut to the same specifications as the PDO support layer to obtain the P4HB toughness layer that matches the PDO layer.
[0028] S3: Composite connection Align and stack the PDO support layer and P4HB toughening layer, place them on the hot press welding machine table, and use a dot-matrix hot press mold (high temperature resistant Teflon material, mold needle diameter 0.5mm). Set the welding parameters as follows: temperature 108℃ (above the melting point of P4HB, within the lower limit range of the melting point of PDO, so that the surface of P4HB monofilament melts, while the PDO monofilament only softens and does not melt; under pressure, the molten P4HB and the surface PDO molecules interdiffusion and form a PDO-P4HB blend structure in situ, which can ensure the adhesion of the two layers without damaging the strength of the monofilament), pressure 0.3MPa, holding time 2~3s. Press the mold evenly over the entire area at 5mm intervals to form a composite connection node. After welding, perform an interlayer peel test to ensure that the peel strength is ≥5 N / cm. For unqualified products, re-hot press according to the above method until the strength requirements are met, to avoid repeated melting and degradation of the material due to secondary hot pressing.
[0029] S4: Edge Enhancement The composite double-layer mesh structure is placed in an injection mold with a pre-reserved molding groove (0.8 mm wide) for the edge reinforcing ring. Molten PDO-P4HB blend material (4:6 ratio, 112~115℃, 5MPa injection pressure) is injected. After injection, the material is kept at a constant temperature and cooled (40~45℃, 10 min) to allow the reinforcing ring to fuse and bond with the monofilaments at the edge of the patch. After cooling, the material is removed, and any remaining flash from the mold is removed with a medical-grade scalpel. The edge of the reinforcing ring is then lightly sanded with sandpaper (sanding until the roughness Ra≤0.8μm). After sanding, the material is rinsed with deionized water to remove any powder residue and avoid postoperative tissue irritation.
[0030] S5: Finished Product Post-Processing The molded patch was immersed in sterile medical ethanol (75% concentration) at room temperature for 30 minutes for disinfection, and then rinsed three times with deionized water (10 minutes each time) to remove ethanol residue; it was then vacuum freeze-dried (temperature -40℃, time 8 hours, vacuum degree -0.09MPa) with the moisture content of the patch controlled to ≤0.5%; finally, after sterility testing (complying with YY / T 0615.1 standard), it was vacuum packaged for later use.
[0031] The patch prepared by the above method includes a patch body with a mesh structure, specifically comprising the following parts: PDO support layer 1 is woven from PDO monofilaments with a diameter of about 0.18 mm and has hexagonal braided holes with a diameter of about 1.0 mm, which are directly attached to the surface of the abdominal wall. The P4HB toughness layer 2 is woven from P4HB monofilaments with a diameter of about 0.22 mm and has diamond-shaped braided holes with a pore size of 1.2~1.5 mm. It covers the side of the PDO support layer 1 away from the abdominal wall and completely overlaps with the PDO support layer 1. Multiple composite connection nodes 3 are a blended structure composed of PDO and P4HB, with a length of 0.35~0.45mm, and are connected at both ends to the PDO support layer 1 and the P4HB toughening layer 2 respectively. The edge reinforcement ring 4 is made of PDO-P4HB blend material (PDO to P4HB ratio is 4:6), with a width of about 0.8mm, surrounds the patch body and covers the edge of PDO support layer 1 and P4HB toughness layer 2.
[0032] Comparative Example 1 A hernia repair patch is prepared using the same weaving process, pore size, and thickness parameters as Example 1, except that medical-grade PGA (molecular weight 120kDa) is used instead of PDO. The finished product includes the following components: The PGA support layer is woven from PGA monofilaments with a diameter of approximately 0.18 mm and has hexagonal braided holes with a diameter of approximately 1.0 mm, which are directly attached to the surface of the abdominal wall. The P4HB toughening layer has diamond-shaped braided holes with a pore size of 1.2~1.5mm, which covers the side of the PGA support layer away from the abdominal wall and completely overlaps with the PGA support layer. Multiple composite connection nodes, a blended structure composed of PGA and P4HB, with a length of 0.35~0.45mm, are connected at both ends to the PGA support layer and the P4HB toughening layer, respectively. The edge reinforcement ring, made of PGA-P4HB blend material (PGA to P4HB ratio of 4:6), is about 0.8mm wide and surrounds the edge of the patch body, covering the PGA support layer and the P4HB toughening layer.
[0033] Comparative Example 2 A hernia repair patch is prepared using the same weaving process, hole shape, diameter, and thickness parameters as Example 1. The difference from Example 1 is that the ratio of PDO to P4HB in the edge reinforcement ring is changed to 2:8. The finished product includes the following components: The PDO support layer is woven from PDO monofilaments with a diameter of approximately 0.18 mm and has hexagonal braided holes with a diameter of approximately 1.0 mm, which are directly attached to the surface of the abdominal wall. The P4HB toughness layer is woven from P4HB monofilaments with a diameter of approximately 0.22 mm. It has diamond-shaped braided holes with a pore size of 1.2~1.5 mm, covers the side of the PDO support layer away from the abdominal wall, and completely overlaps with the PDO support layer. Multiple composite connection nodes, a blended structure composed of PDO and P4HB, with a length of 0.35~0.45mm, are connected at both ends to the PDO support layer and the P4HB toughening layer, respectively. The edge reinforcement ring, made of PDO-P4HB blend material (PDO to P4HB ratio of 2:8), is about 0.8mm wide and surrounds the edge of the patch body, covering the PDO support layer and the P4HB toughening layer.
[0034] Comparative Example 3 A hernia repair patch is prepared using the same weaving process and specifications as Example 1, except that the diameter of the PDO monofilament is increased to 0.25 mm and the diameter of the P4HB monofilament is increased to 0.30 mm. The finished product includes the following components: The PDO support layer is woven from PDO monofilaments with a diameter of approximately 0.25 mm and has hexagonal braided holes with a diameter of approximately 0.7 mm, which are directly attached to the surface of the abdominal wall. The P4HB toughness layer is woven from P4HB monofilaments with a diameter of about 0.30 mm and has diamond-shaped braided holes with a diameter of about 1.0 mm. It covers the side of the PDO support layer away from the abdominal wall and completely overlaps with the PDO support layer. Multiple composite connection nodes, a blended structure composed of PDO and P4HB, with a length of 0.35~0.45mm, are connected at both ends to the PDO support layer and the P4HB toughening layer, respectively. The edge reinforcement ring, made of PDO-P4HB blend material (PDO to P4HB ratio of 4:6), is about 0.8mm wide and surrounds the edge of the patch body, covering the PDO support layer and the P4HB toughening layer.
[0035] Comparative Example 4 A hernia repair patch is prepared using the same weaving process and specifications as in Example 1, but differs in that the PDO support layer is replaced with 1.3mm diamond-shaped large holes (knitted) and the P4HB layer is replaced with 1.0mm hexagonal small holes (woven). The finished product includes the following parts: The PDO support layer is woven from PDO monofilaments with a diameter of approximately 0.18 mm and has diamond-shaped braided holes with a diameter of approximately 1.3 mm, which are directly attached to the surface of the abdominal wall. The P4HB toughness layer is woven from P4HB monofilaments with a diameter of approximately 0.22 mm and has hexagonal braided holes with a pore size of 1.0 mm. It covers the side of the PDO support layer away from the abdominal wall and completely overlaps with the PDO support layer. Multiple composite connection nodes, a blended structure composed of PDO and P4HB, with a length of 0.35~0.45mm, are connected at both ends to the PDO support layer and the P4HB toughening layer, respectively. The edge reinforcement ring, made of PDO-P4HB blend material (PDO to P4HB ratio of 4:6), is about 0.8mm wide and surrounds the edge of the patch body, covering the PDO support layer and the P4HB toughening layer.
[0036] Comparative Example 5 A hernia repair patch differs from Example 1 in that: the double-layer structure is eliminated and replaced with a single-layer structure of PDO-P4HB blend material, wherein PDO:P4HB=5:5; a single-layer weaving method is used, and the finished patch has square holes with a diameter of 1.1 mm and a total thickness of 3.2 mm.
[0037] Comparative Example 6 A hernia repair patch differs from Example 1 in that it is made solely of PDO material and is prepared using the PDO support layer preparation method described in Example 1.
[0038] Comparative Example 7 A hernia repair patch differs from Example 1 in that it is made solely of P4HB material and is prepared using the P4HB toughness layer preparation method described in Example 1.
[0039] Experiment Example 1: Performance Testing of Different Patches Mechanical properties, degradation properties, and biocompatibility were tested on the patches prepared in Example 1 and Comparative Examples 1-5, respectively. Tensile strength was tested according to GB / T 3923.1, and flexural stiffness was tested according to ASTM F3260-25. A 0.1 mol / L PBS buffer (pH=7.4, 37℃) was used to simulate the postoperative in vivo degradation environment. The standard patch samples were immersed in this environment, and the tensile strength at break was tested initially and after 3 months of immersion. Tensile testing was performed using an electronic universal testing machine at a testing speed of 50 mm / min, with a sample width of 10 mm. Five parallel samples were tested in both the warp and weft directions, and the average value was taken after removing extreme values. The test results are shown in Table 1. Table 1. Test results of mechanical properties, degradation properties, and biocompatibility of each group of patches.
[0040] Test results showed that the initial tensile strength of the patch at break was ≥30 N / cm, the interlaminar peel strength was ≥5 N / cm, and after 3 months of simulated in vivo degradation, the tensile strength at break was still ≥20 N / cm, meeting the abdominal wall support requirements 3 months after clinical surgery. All performance characteristics were significantly better than those of comparative examples 1 to 5.
[0041] Experimental Example 2: Biosafety Testing of Fully Absorbable PDO-P4HB Binary Composite Gradient Degradation Hernia Repair Patch For the patches of Example 1 and Comparative Examples 6-7, degradation performance tests were conducted using the method provided in Experimental Example 1. Cytotoxicity, hemolysis, and sensitization tests were performed on the patch of Example 1 according to the methods in GB / T 16886.5-2017, GB / T 16886.4-2022, and GB / T 16886.10-2024, respectively. The test results are shown in Tables 2 and 3, respectively.
[0042] Table 2. Degradation performance test results of each group of patches
[0043] Table 3. Biosafety test results of the patches in the examples
[0044] Test results show that the patch provided in this application has a longer degradation cycle than traditional single-component patches, which can meet the tissue support needs for a longer period of time after surgery, and can eventually be completely degraded without residue; the biosafety test results show that the patch of Example 1 has good biosafety, does not have cytotoxicity or sensitization, and fully meets the clinical safety requirements of medical patches.
[0045] In summary, the fully absorbable PDO-P4HB binary composite gradient degradation hernia repair patch provided by this invention has the following advantages: 1. The composite of two synthetic polymer materials, PDO and P4HB, which are fully absorbable, is used to replace natural animal-derived materials and non-absorbable materials. This eliminates batch-to-batch differences, immunogenicity, and the risk of long-term foreign body irritation from the source. The controllability of the synthetic materials lays the foundation for precise performance adaptation. 2. By precisely controlling the ratio of PDO and P4HB and the composite process, and utilizing the initial high strength and fast degradation rate of PDO and the mid-term flexibility and adaptable degradation rate of P4HB, a gradient performance structure of "short-term high strength support - mid-term flexible transition - late-term complete degradation" is constructed, thereby solving the problem of mismatch between the mechanical and degradation properties of single materials or traditional composite materials. 3. The layered design of “PDO support layer (hexagonal small holes) + P4HB toughness layer (diamond large holes)” is adopted, and PDO-P4HB blend material is used for point hot-press connection nodes to avoid interlayer delamination and stress concentration, thereby balancing strength, anti-adhesion and smooth degradation transition, and improving the synergy between structure and performance. 4. Abandoning metal auxiliary components, the edge reinforcement ring is injection molded using PDO-P4HB (4:6) blend material through the synergistic effect of the intrinsic properties of PDO and P4HB. It is then heat-fused to the main body of the patch, which not only improves the tear resistance of the edge but also achieves full absorbability, thereby simplifying the surgical procedure and avoiding the risks of tissue irritation and stress concentration. 5. Based on the material characteristics of PDO and P4HB, a suitable weaving and lamination composite process is adopted to ensure that the two materials are tightly bonded. This ensures the overall structural stability of the patch while retaining the mesh-like porous structure, providing a suitable microenvironment for cell adhesion, proliferation and tissue ingrowth, and balancing mechanical properties and biocompatibility.
[0046] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A fully absorbable PDO-P4HB binary composite gradient degradable hernia repair patch, characterized in that, The patch body includes a mesh structure and comprises the following parts: PDO support layer, wherein the PDO support layer is adhered to the abdominal wall surface layer; The P4HB toughness layer covers the PDO support layer on the side away from the abdominal wall and completely overlaps with the PDO support layer. Multiple composite connection nodes, wherein each composite connection node is connected at both ends to the PDO support layer and the P4HB toughness layer, respectively. An edge reinforcement ring surrounds the edge of the patch body and covers the edges of the PDO support layer and the P4HB toughness layer; Both the composite connection node and the edge reinforcing ring are made of PDO-P4HB blend material, and the mass ratio of PDO to P4HB in the edge reinforcing ring is 3:7 to 5:
5.
2. The fully absorbable PDO-P4HB binary composite gradient degradable hernia repair patch according to claim 1, characterized in that, The mass ratio of PDO to P4HB in the edge reinforcement ring is 4:
6.
3. The fully absorbable PDO-P4HB binary composite gradient degradable hernia repair patch according to claim 1, characterized in that, The PDO support layer is woven from PDO monofilaments with a diameter of 0.15~0.2mm, and the P4HB toughness layer is woven from P4HB monofilaments with a diameter of 0.2~0.25mm. And / or, the PDO support layer has hexagonal braided holes with a pore size of 0.8~1.2mm, and the P4HB toughness layer has diamond braided holes with a pore size of 1.2~1.5mm.
4. The fully absorbable PDO-P4HB binary composite gradient degradable hernia repair patch according to claim 1, characterized in that, The length of the composite connection node is 0.35~0.45mm; And / or, the width of the edge reinforcing ring is 0.5~0.8mm.
5. The fully absorbable PDO-P4HB binary composite gradient degradable hernia repair patch according to any one of claims 1 to 4, characterized in that, The thickness of the patch body is 3.0~4.0mm, the thickness of the PDO support layer is 1.0~1.5mm, and the thickness of the P4HB toughness layer is 1.8~2.5mm.
6. A method for preparing a fully absorbable PDO-P4HB binary composite gradient-degradable hernia repair patch according to any one of claims 1 to 4, characterized in that, Includes the following steps: Layered molding: Specifically includes the following steps: (1) PDO support layer forming: PDO monofilaments with a diameter of 0.15~0.2mm are woven in a hexagonal weaving method. After weaving, they are heat-set to stabilize the pore size. Then they are cut to the required specifications to obtain the PDO support layer. (2) P4HB toughness layer forming: P4HB monofilament with a diameter of 0.2~0.25mm is woven in a weft knitting diamond mesh. After weaving, it is subjected to low temperature setting treatment and then cut to the same specifications as the PDO support layer to obtain the P4HB toughness layer. Composite connection: The PDO support layer and the P4HB toughening layer are aligned and stacked, and welded using a point-type hot pressing method. Multiple composite connection nodes made of PDO-P4HB blend material are formed in situ between the PDO support layer and the P4HB, so that the PDO support layer and the P4HB toughening layer form a composite double-layer mesh structure; wherein the temperature of the hot pressing welding is higher than the melting point of P4HB and within the lower limit range of the melting point of PDO. Edge reinforcement: An edge reinforcement ring made of PDO-P4HB blend material is formed at the edge of the double-layer mesh structure by injection molding. After cooling, the ring is polished and cleaned to obtain the patch body.
7. The method according to claim 6, characterized in that, In the PDO support layer forming step, the heat setting treatment temperature is 90~95℃ and the time is 2min.
8. The method according to claim 6, characterized in that, In the P4HB toughness layer forming step, the low-temperature setting treatment is performed at a temperature of 40°C for 3 minutes.
9. The method according to claim 6, characterized in that, In the composite connection step, the hot-press welding method is as follows: Under conditions of temperature 106~110℃ and pressure 0.2MPa, press evenly at 5mm intervals, and keep warm for 2~3 seconds after each press.
10. The method according to claim 9, characterized in that, The temperature for hot-press welding is 108°C.
11. The method according to claim 9, characterized in that, The composite connection process also includes the following steps: The double-layer mesh structure after hot-press welding was subjected to an interlayer peel test. Samples with a peel strength ≥5N / cm were selected for edge reinforcement, and the remaining samples were re-hot-press welded.
12. The method according to claim 6, characterized in that, In the edge reinforcement step, the injection molding method is as follows: The double-layer mesh material is placed in an injection mold with a pre-reserved molding groove. Molten PDO-P4HB blend material is injected into the molding groove and injection molded at a temperature of 112~115℃ and a pressure of 5MPa. And / or, the cooling method is as follows: Place the injection-molded sample at 40~45℃ for 10 minutes; And / or, the polishing method is as follows: After cooling, remove any remaining flash from the mold using a medical-grade scalpel, and then lightly sand the edge reinforcement ring with sandpaper until the roughness is ≤0.8μm.
13. The method according to claim 6, characterized in that, Before the PDO support layer forming step, the following steps are also included: Material pretreatment: Medical-grade PDO particles and medical-grade P4HB particles are vacuum dried to a moisture content of ≤0.1%, and the dried PDO particles and P4HB particles are melt-spun to obtain PDO monofilaments and P4HB monofilaments, respectively.
14. The method according to claim 13, characterized in that, The method for drying the medical-grade PDO particles is as follows: Dry at 80℃ and -0.09MPa for 4 hours.
15. The method according to claim 13, characterized in that, The method for drying the medical-grade P4HB particles is as follows: Dry at 50℃ and -0.09MPa for 6 hours.
16. The method according to claim 13, characterized in that, The PDO monofilament is prepared as follows: dried PDO particles are melt-spun at 120~130℃ using a single screw spinning machine to obtain PDO monofilaments with a diameter of 0.15~0.2mm.
17. The method according to claim 13, characterized in that, The preparation method of the P4HB monofilament is as follows: Dry P4HB particles were melt-spun at 80-90℃ using a single-screw spinning machine to obtain P4HB monofilaments with a diameter of 0.2-0.25mm.
18. The method according to claim 6, characterized in that, Following the edge enhancement step, the following steps are also included: Post-processing of finished product: The patch body is soaked in medical alcohol at room temperature for 30 minutes, rinsed with deionized water, and then freeze-dried under vacuum until the moisture content is ≤0.5% to obtain the patch.
19. The method according to claim 18, characterized in that, The freeze-drying method is as follows: Dry for 8 hours at a temperature of -40℃ and a vacuum of -0.09MPa.
Citation Information
Patent Citations
Hernia patch with removable resilient element
CN102137634A
Composite SIS tissue repair materials and their preparation methods
CN103877619B
Complex hernia patch and preparing method and application thereof
CN105311679A
Reinforced absorbable rotator cuff patch
CN118787479A
